The neuroleptic drug fluphenazine induces a significant UVA-mediated cytotoxic effect on three human cancer cell lines through apoptosis. Issue 9 (12th March 2019) - Menilli, Luca; García-Argáez, Aída Nelly; Dalla Via, Lisa; Miolo, Giorgia
Abstract : The cytotoxic activity of fluphenazine (FPZ ) in combination with UVA light was evaluated on three human tumor cell lines, HeLa, MSTO-211H and A431. Abstract : The cytotoxic activity of fluphenazine (FPZ ) in combination with UVA light was evaluated on three human tumor cell lines, HeLa, MSTO-211H and A431. The photobiological effect was determined following irradiation treatment in the presence of/or after the removal of incubatedFPZ . Under both conditions, FPZ proved to be very effective in killing tumor cells, with GI50 values in the micromolar range. However, whenFPZ was present during irradiation, the photocytotoxicity was at least two times higher than that after its removal suggesting the contribution of the drug both outside and inside the cells. The uptake ofFPZ was very fast and, after only 15 minutes of incubation, the compound was accumulated inside lysosomes, as evidenced through fluorescence microscopy.FPZ distribution covered also the nucleus and the cytoplasm without significant plasma membrane association. After irradiation, the membrane of lysosomes in whichFPZ was accumulated lost its integrity suggesting that the released lysosomal enzymes played an important role in cell death, and mitochondria were damaged as well, following apoptosis. Indeed, cytofluorimetric studies demonstrated that apoptosis was the main mechanism of cell death. Finally, an extremely high production of ROS was found, indicating a significant photodynamic mechanism involved in the photocytotoxic effect ofFPZ . Taken together, our data show thatFPZ following UVA irradiation behaves as an effective photoantiproliferative compound inducing apoptosis on various human tumor cells.